Life Cycle Assessment of a Single-family Passive House: Environmental Performance Compared with a Conventional Residential Model - Ratajczak, Maria; Szocik, Jagoda; Sinacka, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper delves into the critical intersection of sustainable development in terms of the residential building with a particular focus on passive house designs and their environmental impacts. Passive houses are distinguished by their exceptional energy efficiency, relying minimally on active heating and cooling systems, which makes them a leading model in sustainable residential construction. Through this research, this paper aims to shed light on the environmental implications of passive house designs by employing Life Cycle Analysis (LCA) as a key evaluative tool.
Keywords: sustainable construction; passive house; energy efficiency; Life Cycle Analysis